1993
DOI: 10.1152/jappl.1993.74.3.1123
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood pressure responses to graded transient arousal from sleep in normal humans

Abstract: During obstructive sleep apnea, transient arousal at the resumption of breathing is coincident with a substantial rise in blood pressure. To assess the hemodynamic effect of arousal alone, 149 transient stimuli were administered to five normal subjects. Two electroencephalograms (EEG), an electrooculogram, a submental electromyogram (EMG), and beat-to-beat blood pressure (Finapres, Ohmeda) were recorded in all subjects. Stimulus length was varied to produce a range of cortical EEG arousals that were graded as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
168
2
15

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(201 citation statements)
references
References 0 publications
16
168
2
15
Order By: Relevance
“…In addition, we found significant cardiovascular changes at event termination despite few CAs, regardless of type, being terminated by arousal. This is consistent with previous studies in adults that have demonstrated that arousals not meeting the ASDA criteria are also associated with significant autonomic changes, albeit smaller than those associated with EEG desynchronization (Davies et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we found significant cardiovascular changes at event termination despite few CAs, regardless of type, being terminated by arousal. This is consistent with previous studies in adults that have demonstrated that arousals not meeting the ASDA criteria are also associated with significant autonomic changes, albeit smaller than those associated with EEG desynchronization (Davies et al, 1993).…”
Section: Discussionsupporting
confidence: 93%
“…The higher night-time risks may also be explained by acute physiologic responses induced by night-time noise events that might affect restoration during sleep. Noise-induced instantaneous autonomic responses during sleep do not only occur in waking hours but also in sleeping subjects even when no (electroencephalogram recorded) awakening occurs (Davies et al 1993). Subjects do not adapt on a long-term basis although a clear subjective habituation occurs after a few nights (Muzet 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation could be that we observed that the mean duration of the respiratory events preceding longer arousals showed a trend to be higher than the duration of events preceding shorter arousals. Davies et al [7] showed that apnea length was an independent predictor of blood pressure rise. They suggested that because the stimulus required for causing arousal increases with the depth of NREM sleep, longer apneas (during which sleep has had longer to become established) may require a more intense arousal response for their termination and, thus, lead to larger peripheral autonomic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The arousal response is important for survival of the affected patient; however, the sleep fragmentation induced by repetitive arousals and the physiological events that surround the arousal response also have adverse consequences which contribute to the pathophysiology and clinical manifestations of SDB [5]. Arousals are characterized by abrupt changes in central nervous system activity that produce electroencephalogram (EEG) activation and marked changes in a wide range of autonomic nervous system parameters such as heart rate (HR), blood pressure (BP), ventilation and peripheral vascular resistance [6][7][8][9][10]. Arousals are typically evident and conventionally detected as changes in cortical EEG activity, a labor-intensive approach associated with high interscorer variability [11].…”
Section: Introductionmentioning
confidence: 99%